Descriptive cataloging for the AACR2R and USMARC : - Millsap, Larry (Neal-Schuman Publishers, 1991)
This workbook is designed to give the catalogers practice in creating original descriptive cataloging records which can be shared with other libraries in an automated environment. It is especially intended for catalogers in small libraries who have neither a great deal of experience making MARC records in many different formats nor more experienced colleagues nearby who can provide advice